Factors affecting anxiety levels of students of the Bachelor of Medicine Study Program and the Doctor's Profession, Faculty of Medicine, Udayana University Class of 2018-2020 in Undertaking the Online Lecture Learning System During the COVID-19 Pandemic (Research, Society and Development, 2022)
Throughout the pandemic of COVID-19, medical students have been undergoing online learning, which has the potential to cause them anxiety. The study’s objective is to determine a relationship between anxiety scales and gender, year of study, resilience scale, and social support scale. This study used a cross-sectional approach with analytic observational methodology. The year of study and gender were in the biodata section, the resilience scale was calculated utilizing the Nicholson McBride Resilience Questionnaire (NMRQ), and the social support scale was calculated utilizing the Oslo Social Support Scale-3 (OSSS-3). The Beck Anxiety Inventory (BAI) was employed to evaluate anxiety scales. The data was examined utilizing univariate and bivariate methods such as Chi-square and Kendall-tau. The amount of respondents was 238 respondents who were selected by simple random sampling. The result showed significant results (p